Electoral System Reforms and Their Effects on the Party System in the Indonesian House of Representatives - Kahfi Adlan Hafiz (Asia-Pacific Journal of Elections and Democracy, 2023)
This study investigates how different legislative electoral codes have evolved since the Reformasi era and how they impact the multiparty system in Indonesia. The study employs a qualitative approach and examines secondary data sources through a literature review. The research uncovers two main findings. Firstly, the legislative election system in Indonesia has experienced significant changes since the Reformasi era of 1998, including variations in proportional system models, district magnitude, electoral and parliamentary thresholds, and electoral formulas. Secondly, changes in the legislative electoral format are likely to influence the structure of the multiparty system in the DPR. To assess the impact of electoral system changes on the multiparty system in the post-Reformasi parliament, the study utilizes the effective number of parties and the Laakso and Taagepera Index. However, the results indicate an insignificant effect.